ANALISIS PREDIKSI EFEK ANTIINFLAMASI PADA PIPER PORPHYROPHYLLUM SECARA IN SILICO - Prayoga, Tria; Rahmat, Deni; Sandhiutami, Ni Made Dwi; Desmiaty, Yesi (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2025)
This study aims to predict the anti-inflammatory effects of compounds in Piper porphyrophyllum using in silico methods. The compounds were analyzed using AutoDock software to evaluate their binding potential with the target protein and Lipinski's rule of five to assess their drug-likeness based on pharmacokinetic properties. Qualitative results show that compounds such as 4'-hydroxy-3',5,7-trimethoxyflavone, 4',5-dihydroxy-3',7-dimethoxyflavone, and 5-hydroxy-3',4',7-trimethoxyflavone form significant interactions with key residues on the target protein. Quantitatively, these compounds exhibit more negative binding free energy compared to the natural ligand (-7.34 kcal/mol), with values of -8.35 kcal/mol, -8.13 kcal/mol, and -8.20 kcal/mol, respectively, indicating stronger binding affinity. Evaluation using Lipinski's rule shows that these compounds meet the criteria as potential drug candidates. In conclusion, this in silico method can predict the potential of Piper porphyrophyllum compounds as anti-inflammatory agents, supporting further research for experimental validation.